PENATALAKSANAAN FISIOTERAPI DENGAN MODALITAS YOGA VILOMA PRANAYAMA, DAN DIAPHRAGMATIC BREATING EXERCISE TERHADAP PENURUNAN NYERI DAN SESAK NAFAS PADA PASIEAN ASTHMA BRONCHIAL - Kurniani Fatma Hardini; Alfian Noha Zulkarnaen, Dafa Paksi Kirana (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Bronchial asthma is chronic inflamation of the lungs due to allergies, weather, infection, pollution or due to daily active or passive smoking person. Problems in bronchial asthma in the form of shortness of breath and pain in the respiratory muscles so that physiotherapy treatment is needed in the form of physiotherapy management in the yoga viloma pranayama and diaphragmatic breating exercis. This physiotherapy treatment was given for 3 weeks with 2 meeting per week at RS Paru Manguharjo in Madiun city on january 5-20 january 2022 using the case study method. The phyhsiotherapy modalities of yoga viloma pranayama and diaphragmatic breathing exercise can reduce pain in the respiratory muscles and decrease the degree of dispnoe in patients with a treatment 10 minutes and 30 second rest for each session